2020
DOI: 10.1080/21580103.2020.1758801
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of various pretreatment on seed germination of Dalbergia cochinchinensis

Abstract: Dalbergia cochinchinensis belongs to family Fabaceae, is a hardwood tree species listed as vulnerable on the IUCN Red List of Threatened Species. This species is a slow-growing and it is threatened by overexploitation for its timber and illegal logging. Because of the increased demand for the timber, the species is rapidly disappearing in many habitats and threatened to extinction in the near future. Prevention of illegal logging and conservation efforts are required to protect the species. Seed germination an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In addition, soaking seeds in warm water has the effect of softening the seed coat and increasing the permeability of the seed coat. Therefore, warm water soaking at a suitable temperature is beneficial for seed germination (Chen et al, 2017;Seng and Cheong, 2020;Yousif et al, 2020). This study confirmed that exogenous GA3 and warm water soaking treatments are beneficial to the dormancy breaking and germination of E. ulmoides seeds.…”
Section: Effects Of Different Soaking Treatments On the Germination O...supporting
confidence: 61%
“…In addition, soaking seeds in warm water has the effect of softening the seed coat and increasing the permeability of the seed coat. Therefore, warm water soaking at a suitable temperature is beneficial for seed germination (Chen et al, 2017;Seng and Cheong, 2020;Yousif et al, 2020). This study confirmed that exogenous GA3 and warm water soaking treatments are beneficial to the dormancy breaking and germination of E. ulmoides seeds.…”
Section: Effects Of Different Soaking Treatments On the Germination O...supporting
confidence: 61%
“…The probable reason for reduced seedling emergence might be attributed to the fact that increased temperature affected the physiological activities of the embryo of seeds. However, several studies reported that hot water treatment could improve the germination of seeds and several other plant species (Azad et al 2012;El-Sayed et al 2013;Das 2014;Suleiman et al 2018;Seng and Cheong 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers working on breaking dormancy such as Rady and El-Yazal [15], Rady and El-Yazal [16] El-Yazal and Rady [17] El-Yazal et al [18] El-Yazal and Rady [19] El-Yazal and Rady [20] El-Yazal et al [21] El-Yazal et al [22] El-Yazal et al [23] El-Yazal et al [24] El-Yazal et al El-Yazal [26] on buds and Şan [1], Mark [27], Keun et al [28], Pliszko and Kostrakiewicz-Gierałt [29], Pliszko and Kostrakiewicz-Gierałt [30] Pliszko and Kostrakiewicz-Gierałt [31] Górnik et al [32] on seeds. The beneficial effect of stratification on seed germination was studied by Seng and Cheong [33] Yan and Chen [34] Guo et al [35].…”
Section: Introductionmentioning
confidence: 99%